A Study on Leveraging Sensors and AI in Insect-Inspired Robotics for Unstructured Environments: Bio-Inspired Autonomy - Heena T. Shaikh; I.R. Kazi Kutubuddin Sayyad Liyakat (International Journal of Robotics and Automation in Mechanics, 2025)
Insects, with their unparalleled agility, resilience, and highly efficient sensory-motor control in complex, unstructured environments, offer a rich blueprint for the next generation of autonomous robots. This study explores the design, implementation, and potential of insect-inspired robots, focusing on the synergistic integration of miniaturized sensor arrays and advanced Artificial Intelligence (AI) algorithms. We delve into bio-mimetic sensing, drawing inspiration from compound eyes, olfactory systems, and tactile hairs, to equip robots with acute environmental perception, obstacle avoidance capabilities, and navigation in cluttered spaces. Furthermore, we present how AI, including machine learning for pattern recognition, reinforcement learning for adaptive locomotion, and swarm intelligence algorithms for coordinated behavior, translates raw sensor data into intelligent decision-making and robust autonomous actions. The study demonstrates a significant leap towards developing micro-robots capable of traversing difficult terrains, performing intricate inspection tasks, and operating effectively in environments inaccessible or hazardous to humans, offering transformative potential across diverse fields from search and rescue to environmental monitoring and precision agriculture.
Keywords: Insect; Robot; artificial intelligence; bio-inspired; sensors